The art of war - Rankin, D; Deana M. Rankin (1999)
﻿ 'The Art of War' studies the transition of the soldier from fighter to settler as it is reflected in the texts he produces. Drawing on texts written by soldiers, in English, between c. 1624 and 1685, it focuses on representations of events in Ireland from 1641-1655, that is to say, during the Catholic Confederation and the Cromwellian campaigns and settlement. The focus and methodology of the thesis seek to restore a more literary reading of seventeenth century texts from, and about, Ireland to the current vibrant historical debate on the period. It argues that the writings of the Old Irish, Old English, New English, and Cromwellian soldiers in Ireland draw on a variety of literary influences – the traces of Guicciardini and Machiavelli, Sidney and Spenser are clear. It also charts shifts in the genres of military writing from professional handbooks, to documents of civil policy, to romance, poetry, and the theatre. In doing so, it addresses the literary tools which the soldier-writer uses to define the self within a complex network of political, national, religious, and personal allegiances. The thesis is divided into three parts. The first, chapter one, explores the trafficking of military images between military handbook and literary text. It pays particular attention to Ireland as a borderland for the European Wars and the English colonial enterprise. The second part, comprising three chapters, examines three different perspectives on the Irish Wars. The first, that of the Old English writer Richard Sellings; the second, that of the anonymous Aphorismical Discovery; the third begins with a view of the 'Irish enemy' from England, as it is constructed and enforced in the pamphlet literature of the Civil War period, and ends with the perspective of Richard Lawrence, a Cromwellian soldier-turned-settler in the early 1680s. The third part, the fifth and final chapter, explores the controversies surrounding recent Irish history as they are played out in the wake of the Exclusion Crisis. This is followed by a brief conclusion.